The anti-Jacobin novel - Grenby, Matthew O. (Cambridge University Press, 2001)
The French Revolution sparked an ideological debate which also brought Britain to the brink of revolution in the 1790s. Just as radicals wrote 'Jacobin' fiction, so the fear of rebellion prompted conservatives to respond with novels of their own; indeed, these soon outnumbered the Jacobin novels. This was the first survey of the full range of conservative novels produced in Britain during the 1790s and early 1800s. M. O. Grenby examines the strategies used by conservatives in their fiction, thus shedding new light on how the anti-Jacobin campaign was understood and organised in Britain. Chapters cover the representation of revolution and rebellion, the attack on the 'new philosophy' of radicals such as Godwin and Wollstonecraft, and the way in which hierarchy is defended in these novels. Grenby's book offers an insight into the society which produced and consumed anti-Jacobin novels, and presents a case for reexamining these neglected texts.
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Englisch; Roman; Jakobiner; Konservativismus; Französische Revolution